Corona field effect surface passivation of n-type IBC cells - Bonilla, R; Wilshaw, P; Reichel, C; Hermle, M (Elsevier, 2016)
Passivation of silicon surfaces is an important requirement in achieving high energy conversion efficiencies in interdigitated back contact cells. Surface passivation, commonly achieved by dielectric coatings, can be greatly improved by extrinsic addition of chemical and field effect components. In particular, cell performance is strongly dependent on front surface passivation. In this work device modelling is used to show that 200% relatively better performance can be achieved using charge extrinsically added to a passivation coating without the need for a front surface field. Research scale cells have been tested as a function of front surface corona charge. On average an absolute improvement in efficiency of 0.3% ±0.3 and 0.13% ±0.12 has been observed on cells without and with a front surface field. These results show that extrinsic field effect passivation can produce significant improvements in cell efficiency.